Community Perspectives on Elephant Conservation in Eastern Nepal - Bhandari, Bishal; KC, Nishan; Chaudhary, Nirmal; Gautam, Shreejan; Dhami, Bijaya; GC, Aashish; Neupane, Bijaya (Banko Janakari, 2025)
Understanding people’s attitudes towards elephants (Elephas maximus) is crucial for formulating appropriate policies for species conservation and mitigating human-elephant conflict (HEC). Therefore, this study aimed to assess attitudes and perceptions toward elephant conservation in Udayapur District, eastern Nepal. Based on information from key informants (n = 10) and focus group discussions (n = 3), a total of 97 households were selected for a semi-structured questionnaire survey to collect data on human-elephant incidents. Half of the respondents (50%) identified crop damage as the primary issue caused by wild elephants, and nearly half (46%) reported an increase in HEC over the past five years (2016–2020). The majority (60%) claimed habitat encroachment as a major cause of HEC in the study area. Approximately 46% of respondents use fire-related techniques to mitigate such conflicts. Moreover, more than half of the respondents (62%) showed a low willingness to conserve elephants, which was significantly influenced by their education level [χ2 (2) = 9.43, p < 0.001] and occupation [χ2 (2) = 7.81, p < 0.05]. The findings of this study will help develop management interventions that benefit communities and elephants through effective HEC mitigation.